Legal analysis of Complementary Law No. 214/2025: the role of green fiscal instruments in a sustainable transition (Revista do Tribunal Regional Federal da 3ª Região, 2025)
The study analyzes the relationship between the constitutional right to an ecologically balanced environment and the fiscal mechanisms introduced by the recent Brazilian tax reform. The 1988 Constitution recognizes the environment as a fundamental right and links its protection to the dignity of the human person, assigning responsibilities to both the State and society. In turn, Constitutional Amendment No. 132/2023 and Complementary Law No. 214/2025 introduce a new perspective by incorporating fiscal instruments aimed at sustainability. Accordingly, this work seeks to understand how the reform may influence environmental protection and the transition toward a sustainable economic model. To this end, it employs a qualitative approach, with bibliographic and documentary analysis of legal sources, in order to map in detail the structural changes with environmental interfaces, identify green tax instruments, analyze the most affected economic sectors, and assess the resulting environmental implications. The findings indicate that the selective tax has significant potential to discourage polluting practices and encourage more sustainable consumption patterns, although its effectiveness depends on careful regulation. It is observed that sectors such as energy, transportation, and extractive industry tend to be the most affected, with relevant impacts on reducing pollutant emissions and fostering the adoption of clean technologies. Therefore, the tax reform, by aligning revenue collection with sustainability, can contribute to building a low-carbon economy, provided that the instruments are applied with normative coherence and attention to sectoral specificities.
Keywords: tax reform; environment; green taxation; selective tax; extrafiscality; sustainable development